PENERAPAN KAIDAH MAQÂSHID SYARIAH DALAM PRODUK PERBANKAN SYARIAH - Nurnazli, Nurnazli (Universitas Islam Negeri Raden Intan Lampung, 2014)
Maqâshid Syari‟ah refers to an act of achieving andprotecting the benefits and good (masalih) for the sake ofhuman beings. In fulfilling the maqâshid al Syari‟ah, maninadvertently fulfills not only his social and ethical needsbut also his commercial needs as well. There lies thewisdom of Muslims having to “fulfill all obligations” as indoing so mankind is fulfilling one another‟s needs andobligations, hence a win-win for all. The current practiceof Islamic banks needs to incorporate maqâshid al-Syari‟ahinto their management strategy to ensure its sustainabilityto serve mankind in the future, in confirmation to therequirement of Syari‟ah. Though profitability is essentialand must be achieved, but it is not the main objective. InIslam, the ultimate objectives of any activities includingbusiness activities are ultimately with the aim of achievingobjectives of Syari‟ah or maqâshid al-Syari‟ah.